HUBUNGAN ANTARA TINGKAT PENGETAHUAN BIDAN TENTANG ASAM FOLAT DENGAN PRAKTEK SUPLEMENTASI ASAM FOLAT KEPADA IBU HAMIL - Natalia, Shanty (STRADA : Jurnal Ilmiah Kesehatan, 2012)
The concept of evidence-based states that the use of folic acid during pre and perikonsepsi reduce the risk of brain damage, neural disorders, spina bifida, and anencepalus on the fetus. Folic acid is also useful to help the production of red blood cells, DNA synthesis in fetal and placental growth. The scope of midwifery care for pregnant women included in the standard midwife-3 is one of competency assess nutritional status of pregnant women and its relation to fetal growth. The purpose of this study is to determine the relationship between the level of knowledge of midwives and practice of folic acid supplementation for pregnant mothers. This study used an analytic observational method with cross sectional, and samples were taken by quota sampling. Subjects were 42 private practice midwives who work area measuring Surakarta. Used in the form of questionnaires and medical records. Data were analyzed using Fisher’s statistical test (α = 0.05). The results of the 42 respondents indicated that most respondents have a level of knowledge about folic acid is enough for 21 respondents (50%), while folic acid supplementation in practice, most respondents did fine that is equal to 26 respondents (61.90%) . Statistical analysis showed the significant value of 0.483 (p> 0.05). The conclusion of this research is that there is no relationship between knowledge and practice of folic acid supplementation, in the sense of high and low knowledge of a midwife does not affect the practice of folic acid supplementation to pregnant mothers.